1997
DOI: 10.1210/jc.82.10.3342
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Catecholestrogen Metabolism to Acute Graded Exercise in Normal Menstruating Women before and after Training

Abstract: It has been hypothesized that exercise-related hypo-estrogenemia occurs as a consequence of increased competition of catecholestrogens (CE) for catechol-O-methyltransferase (COMT). This may result in higher norepinephrine (NE) concentrations, which could interfere with normal gonadotropin pulsatility. The present study investigates the effects of training on CE responses to acute exercise stress. Nine untrained eumenorrheic women (mean percentage of body fat +/-SD: 24.8 +/- 3.1%) volunteered for an intensive 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…However, other studies (4,13,14) show that variations in the estrogen and progesterone levels during the MC, affect the feminine physiology in many factors such as: use of energetic substrate in different training intensities and volumes, oxygen consumption, energetic substrate storage and fats oxidation. Yet, these physiological changes did not demonstrate significant alterations in the flexibility levels in the three phases of the MC of the actual study.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies (4,13,14) show that variations in the estrogen and progesterone levels during the MC, affect the feminine physiology in many factors such as: use of energetic substrate in different training intensities and volumes, oxygen consumption, energetic substrate storage and fats oxidation. Yet, these physiological changes did not demonstrate significant alterations in the flexibility levels in the three phases of the MC of the actual study.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been hypothesized that exercise may alter estrogen metabolism in a manner that could alter cancer etiology (17). We are aware of several prior studies that have examined the effects of exercise training on estrogen metabolism among premenopausal women (18)(19)(20)(21) and one in postmenopausal women (17). Of these, only one (22) has observed an intervention effect on the 2:16 ratio in a subset of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is the first to examine the effect on the 2:4 ratio. Three publications reported on the observed effects of 5 days of intensive aerobic exercise training on estrogen metabolites (19)(20)(21). None of these studies noted significant changes in metabolites during the follicular phase, but significant decreases were noted for 2-hydroxyestrogens after 5 days of intensive training during the luteal phase (20).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in two studies, in which an aerobic exercise intervention was conducted over 12 weeks for eumenorrheic pre-menopausal women [84] in one study and over 12 months for the post-menopausal women in the other study [85], the urinary excretion of 2-OHE 1 and 16a-OHE 1 or their ratio was not significantly altered. However, two other studies [86,87] showed that exercise training promoted the formation of 2-MeOE 2 and 4-MeOE 2 , which may favorably alter breast epithelial cell proliferation [29]. These studies investigated the effect of exercise training over two consecutive menstrual cycles, and reported that the 2-MeOE 2 / 2-OHE 2 and 4-MeOE 2 /4-OHE 2 level ratios were higher post-training, indicating the possible protective effects of sports participation against breast cancer [86,87].…”
Section: Breast Epithelial Cell Proliferationmentioning
confidence: 93%
“…However, two other studies [86,87] showed that exercise training promoted the formation of 2-MeOE 2 and 4-MeOE 2 , which may favorably alter breast epithelial cell proliferation [29]. These studies investigated the effect of exercise training over two consecutive menstrual cycles, and reported that the 2-MeOE 2 / 2-OHE 2 and 4-MeOE 2 /4-OHE 2 level ratios were higher post-training, indicating the possible protective effects of sports participation against breast cancer [86,87]. Thus, epidemiological studies that have been performed to date, including the exercise interventional studies, provide some support for exercise producing favorable changes in a woman's pattern of estrogen metabolism related to breast cancer risk.…”
Section: Breast Epithelial Cell Proliferationmentioning
confidence: 93%